Pengimplemetasian Asas dalam Hukum Perikatan Khususnya Asas Konsensualisme - Gusti Ayu Sri Krisnayanti; A.A. Istri Eka Krisna Yanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research have intenions to show and understand the legal principles of engagement in agreements when entering into agreements. know about the implementation of the principles of engagement, especially the principle of consensualism in realizing an engagement. The writing of this article applied through the normative legal research method where the author employs a legislative approach and a system of legal concept. The study results indicate that when making an agreement, several principles serve as the foundation of legal proceedings, guiding decisions and actions within the judicial system, as a legal basis this principle can provide an overview of the contract. Numerous guiding principles are available for reference and implementation in various contexts and situations. The principles of association include the principle of freedom of contract, the principle of good faith, the principle of pacta sunt servada, and the principle of consensualism. In implementing consensualism in a contract such as an online buying and selling agreement. Buying and selling online from the point of view of contract law in Indonesia uses Paragraph (1) of Article 18 of the Electronic Information and Transactions Law. There is also a lease agreement where the parties make an agreement. The legal basis for renting a house is explained in Government Regulation no. 44 of 1994, which guarantees legal protection for home owners or tenants. The regulation also explains that a rental agreement can be said to be valid if there is approval or permission from the owner of the dwelling. In accordance with the basic law of renting a house, there are 3 (three) clauses in the house rental agreement